Between catholic doctrine and ideas of progress. The modern imprint of the bavarian capuchin missionary Sigifredo de Frauenhäusl in Araucania (1905-1923) - Fabregat Peredo, Mario Rodrigo (Revista de Historia Social y de las Mentalidades, 2025)
This paper has the objetive of identify expressions of modern thought and the probable handling of some scientific theories by the Bavarian Capuchin missionaries in Araucania at the end of the 19thcentury and the beginning of the 20th century. It focuses on the missionary Sigifredo de Frauenhäusl, who served in the Mission of San Sebastián de Panguipulli, in the province of Valdivia. Documentation —such as letters and missionary chronicles— written by him between the years 1905 and 1923 was reviewed. It is concluded that in Sigifredo one observes a mentality embedded within the patterns of modernity and the idea of progress, a stance that does not obscure his deep missionary vocation. Manifestations associated with the appreciation of Western medicine, the potential of nature and the social impact of the press can be seen.
Keywords: Sigifredo de Frauenhäusl; bavarian capuchin missionary; modernity; science; progress; La Araucania